Beans (Phaseolus ssp.) as a Model for Understanding Crop Evolution - Bitocchi, Elena; Rau, Domenico; Bellucci, Elisa; Rodriguez, Monica; Murgia, Maria L.; Gioia, Tania; Santo, Debora; Nanni, Laura; Attene, Giovanna; Papa, Roberto (Frontiers in Plant Science, 2017)
Here, we aim to provide a comprehensive and up-to-date overview of the most significant outcomes in the literature regarding the origin of Phaseolus genus, the geographical distribution of the wild species, the domestication process, and the wide spread out of the centres of origin. Phaseolus can be considered as a unique model for the study of crop evolution, and in particular, for an understanding of the convergent phenotypic evolution that occurred under domestication. The almost unique situation that characterises the Phaseolus genus is that five of its ~70 species have been domesticated (i.e., Phaseolus vulgaris, P. coccineus, P. dumosus, P. acutifolius, P. lunatus), and in addition, for P. vulgaris and P. lunatus, the wild forms are distributed in both Mesoamerica and South America, where at least two independent and isolated episodes of domestication occurred. Thus, at least seven independent domestication events occurred, which provides the possibility to unravel the genetic basis of the domestication process not only among species of the same genus, but also between gene pools within the same species. Along with this, other interesting features makes Phaseolus crops very useful in the study of evolution, including: (i) their recent divergence, and the high level of collinearity and synteny among their genomes; (ii) their different breeding systems and life history traits, from annual and autogamous, to perennial and allogamous; and (iii) their adaptation to different environments, not only in their centres of origin, but also out of the Americas, following their introduction and wide spread through different countries. In particular for P. vulgaris this resulted in the breaking of the spatial isolation of the Mesoamerican and Andean gene pools, which allowed spontaneous hybridization, thus increasing of the possibility of novel genotypes and phenotypes. This knowledge that is associated to the genetic resources that have been conserved ex situ and in situ represents a crucial tool in the hands of researchers, to preserve and evaluate this diversity, and at the same time, to identify the genetic basis of adaptation and to develop new improved varieties to tackle the challenges of climate change, and food security and sustainability.